Dysregulated calcium signaling in the aged primate association cortices: vulnerability to Alzheimer’s disease neuropathology - Arnsten, Amy F. T.; Perone, Isabella; Wang, Min; Yang, Shengtao; Uchendu, Stacy; Bolat, Dinara; Datta, Dibyadeep (Frontiers in Aging Neuroscience, 2025)
The common, late onset form of Alzheimer’s disease (AD) selectively impacts higher brain circuits, with tau pathology and neurodegeneration preferentially afflicting glutamatergic neurons in the limbic and association cortices. Understanding this selective vulnerability may help reveal the etiology of sporadic AD and therapeutic targets for prevention. The current review describes that these vulnerable circuits express magnified calcium signaling needed for higher cognition and memory, but that heightened calcium signaling becomes toxic when dysregulated by age and inflammation. Many of the earliest pathological events in AD are challenging to study in human brain, as proteins such as tau rapidly dephosphorylate postmortem. However, they can be studied in aging macaques, who are all APOE-ε4 homozygotes and naturally develop cognitive deficits, calcium dysregulation, synapse loss, tau and amyloid pathology and autophagic degeneration, including elevated plasma pT217Tau, a new blood biomarker of incipient AD. High resolution nanoscale imaging of aging macaque brains reveals the earliest stages of soluble tau pathology and its relationships with Aβ42 and calcium signaling. These data indicate that inflammation erodes regulation of calcium signaling leading to the activation of calpain-2, which drives tau hyperphosphorylation, APP cleavage to Aβ42 and autophagic degeneration. These in turn propel further calcium dysregulation to drive vicious cycles. Restoring calcium dysregulation, e.g., with calpain-2 inhibitors, thus may be a rational strategy for slowing or preventing AD pathology. Recent data show that an agent that reduces GCPII inflammation and restores mGluR3 regulation of calcium reduced tau pathology in aged macaques, encouraging this approach. Targeting inflammation and dysregulated calcium may be especially helpful for patients who are APOE-ε4 carriers and insufficiently aided by current anti-amyloid antibody treatments.